Alarm and Tracking System Design of Vehicle Theft via Mobile Phone - Orphomma, Sounith; Soukhavong , Sengthong; Yang, Somboun (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
This paper to design of vehicle alarm and tracking system when someone loses it via notification to mobile phone. The study and design of this time is needed to be comfortable, safe, modern can be used to alert the safety of any vehicle, whether it is motorbike or car. The purpose of this research is to apply and take advantage of the advancement of electronic technology and communication, using a vibration sensor as detector when moving, using the GPS module as a satellite signal detector to identify the location of the device, using a SIM900 module with the same capabilities as the phone. Call and send text messages (SMS) to your mobile phone. The Arduino board is a microcontroller board that acts as a master device that processes and controls all operating systems. The alarm is immediately alerted when the theft occurs with buzzer; At the same time, the system will notify to user’s mobile phone and if we want to know the location of the device or vehicle, we can call the system so that the SIM900 module sends a message telling the current location of vehicle back in the form of the link google maps, making it possible to know the exact positioning. From the exploratory experiments, it is clear that the system designed and built can work property and accurately 100%. The system to be adopted in implement real tasks and be a guide for future development to use in the security alert system and follow up on any other case.